The climate of the interior of Mizuho Plateau - Inoue, Jiro; Nishimura, Hiroshi; Satow, Kazuhide (1983)
P(論文) The scheme and results of the mobile meteorological observation on Mizuho Plateau, East Antarctica are reported. The surface wind and temperature at 4 temporary stations on the traverse route were compared with those of Mizuho Station during the same period. Each station is classified under the category of cold katabatic or cold interior climate though the transitional status is revealed for the latter. Evident decrease of surface wind towards inland is due to the decrease in the surface inclination. The increase in the temperature lapse rate towards inland resulting from the lowering of minimum temperatures is caused by the weakness of the surface wind when the minimum temperature is present as well as by the light breeze of the inland. It is also caused by the decrease of the effect of synoptic disturbance. The surface prevailing wind at V142 (upper end of the plateau) is supposed to be originated from further interior. The small inversion and the locally produced northerly wind was present when the general wind was blocked at V142. The cooling of the atmosphere over V142 is commenced either from the surface or from the height of lower troposhere. The development of the surface inversion is restrained by the successive warm advection from the upper atmosphere. Though the upper air circulation over V142 is not alike over the coast, the warming occurs simultaneously on an occasion of remarkable warm advection. departmental bulletin paper